2004
DOI: 10.1620/tjem.203.211
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Resistance to Oxidation in Patients with Type 2 Diabetes Mellitus

Abstract: We investigated lipid peroxidation, resistance of plasma and red blood cells to oxidation, and antioxidant defense system in erythrocytes and sera in patients with type 2 diabetes mellitus. One group included newly diagnosed 20 patients and the other included 20 patients treated with oral antidiabetic agents (OAD). Twenty healthy subjects served as controls. Serum and red blood cell malondialdehyde (MDA), glutathione (GSH), resistance to oxidation, and plasma thiol (total -SH) levels were measured. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
65
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 41 publications
18
65
0
5
Order By: Relevance
“…The present results indicated the elevation of lipid peroxidation under diabetes. Other studies also reported that the formation of lipid peroxidation products in serum and tissues under diabetes is elevated (42,43), and leads to diabetic complications including retinopathy and neuropathy (44,45). The decrease in lipid peroxidation by the BuOH fraction from the broccoli flower implies a protective role against diabetic oxidative stress induced by STZ.…”
Section: Discussionmentioning
confidence: 94%
“…The present results indicated the elevation of lipid peroxidation under diabetes. Other studies also reported that the formation of lipid peroxidation products in serum and tissues under diabetes is elevated (42,43), and leads to diabetic complications including retinopathy and neuropathy (44,45). The decrease in lipid peroxidation by the BuOH fraction from the broccoli flower implies a protective role against diabetic oxidative stress induced by STZ.…”
Section: Discussionmentioning
confidence: 94%
“…ROS are also produced in the organism as a part of the primary immune defense. [22][23][24][25][26] Phagocytic cells such as neutrophils, monocytes, or macrophages defend against foreign organism by synthesizing large amount of superoxide anion radical and nitric oxide radical as a part of their killing mechanism. To counteract the prooxidant load a diversity of antioxidant defense systems are operative in biological systems including enzymatic and nonenzymatic antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Serum protein thiols have been found to be decreased in patients that are suffering from complications of type 2 diabetes mellitus 37 . There have been reports on decreased plasma thiol levels in diabetic patients 38 . Substantial reduction in plasma-SH (P-SH) levels in diabetic hemodialysis (DHD) patients compared with the level in healthy participants and DM patients.…”
Section: Diabetes Mellıtus and Oxidative Stressmentioning
confidence: 99%